ANALISIS EFISIENSI BOILER FIVES CHAIL BABCOCK BR 2-39-62 KAPASITAS 55 TON/JAM TEKANAN KERJA26 BAR DI PT. PG. RAJAWALI II UNIT PG. JATITUJUH - Tarsudin, Tarsudin; Koswara, Engkos; Susandi, Dony (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2019)
PT. PG. Rajawali II unit PG. Jatitujuh uses 3 boiler units as its energy source, one of which is boiler Fives Cail Babcock BR 2-39-62 capacity of 55 tons / hour. Boilers or boilers are closed vessels used to produce steam, steam is obtained by heating a vessel containing water with fuel. The steam produced by the boiler will be used to drive the turbine in 2 alternators, 1 unit of unigator, 1 unit of mill, 1 unit of cane cuter, and the process of drying sugar. BR 2-39-62 FCB boilers began operating in 1980, this boiler is quite old so that the performance has decreased. For this reason, an analysis was held to determine the efficiency of the boiler. The initial standard of boiler operation FCB 2-39-62 in 1980 was a maximum working pressure of 26 bar, the temperature of the incoming water was 105ºC, steam temperature was 350ºC, steam flow was 47 Ton / Hour, and water quality was 7.0 pH. Based on data and analysis, it is known that the initial efficiency of boiler operation FCB BR 2-39-62 is 100%, while the greatest efficiency on October 21, 2018 is 38%. The effect of decreasing boiler efficiency is caused by the reduced temperature of boiler intake due to the buildup of scale and rust on the pipe, which affects the steam flow.